Keterlibatan dalam Kegiatan dan Kesejahteraan Subjektif Mahasiswa - Muhana S. Utami (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Subjective well being is one indicator of individualʹs and society quality of life. This study aimed to examine the studentʹs involvement on activity and gender as predictors of subjective well being. The participants in this study were 271 undergraduate student at Psychology Study Program of Psychological and Social Culture Science Faculty of Indonesian Islamic University (78,23 % female, and 21,77% male). Participants responded to a questionnaire consisting of involvement of student on activity. Subjective well being was measures by three scales: (1) The SWB‐SWLS (positive affect, negative affect, and global life satisfaction); (2) The SWB – SLS Scale (positive affect, negative affect, and life satisfaction at campus); and (3) The SWB–PLS Scale (positive affect, negative affect, and personal life satisfaction. The parametric statistic method of t – test and nonparametric method of test‐U Mann Whitney analysis showed that the student involvement in extracurricular, profit, and various activities had higher subjective well being than the student didn’t involved in any activities. Nevertheless, this study showed that there was no difference of subjective well being between female and male.